2015 7th International Conference on Games and Virtual Worlds for Serious Applications (VS-Games) 2015
DOI: 10.1109/vs-games.2015.7295773
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing User Engagement in Immersive Games through Multisensory Cues

Abstract: In this article, we report on a user study investigating the effects of multisensory cues on triggering the emotional response in immersive games. Yet, isolating the effect of a specific sensory cue on the emotional state is a difficult feat. The performed experiment is a first of a series that aims at producing usable guidelines that can be applied to reproducing similar emotional responses, as well as the methods to measure the effects. As such, we are interested in methodologies to both design effective sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The study showed that the fusion of individual input signals can increase the accuracy of the engagement detection. Similarly, other researchers have proven that the accuracy in affect recognition tasks is increased by using multi-sensor approaches [48] [49].…”
Section: Related Workmentioning
confidence: 87%
“…The study showed that the fusion of individual input signals can increase the accuracy of the engagement detection. Similarly, other researchers have proven that the accuracy in affect recognition tasks is increased by using multi-sensor approaches [48] [49].…”
Section: Related Workmentioning
confidence: 87%
“…Multisensory feedback can enhance many of the high and complex cognitive processes involved in VR [41]. Particularly, multimodality can trigger different emotional responses in immersive games: Kruijff et al [94] investigated those emotional effects and proposed guidelines that can be applied to reproduce diverse emotional responses in multimodal games. Within the wide area of entertainment, cinematographic and narrative experiences in VR have been emerging during the last years.…”
Section: Entertainmentmentioning
confidence: 99%
“…As some of those aforementioned works have shown, multisensory cues can trigger different users' emotional responses in immersive games. Kruijff et al [83] reported another work where they investigated those effects and proposed guidelines that can be applied to reproduce similar emotional responses. Whether because of emotional responses or because of the complexity of the games, cognitive loads can be quite high.…”
Section: Entertainmentmentioning
confidence: 99%

Multimodality in VR: A survey

Martin,
Malpica,
Gutierrez
et al. 2021
Preprint